PENGERTIAN, PERSAMAAN DAN PERBERADAAN ANTARA TAFSIR DAN TA’WIL AL-QURAN - Aisyah, Noor (Al-Manba, 2023)
Tafsir is intended as an outward meaning of the Qur'an while ta'wil is an attempt to understand the outward meaning of the Qur'an. In the understanding between interpretation and ta'wil of the Koran, there are some scholars who equate interpretation and ta'wil of the Koran, but there are also those who distinguish between interpretation and ta'wil of the Koran. Interpretation of the al-Qur’an in terms of explaining the meaning of the verses of the al-Qur’an, most of which are still in a very global (general) form which supports the understanding of the interpretation of the al-Qur’an covering various sciences such as: Science of Sharf, Nahwu , Science I'rab, Mufradat, Ma'ani, Bayan. While the meaning of ta'wil al-Qur’an in language, the word ta'wil comes from the word ala-yaulu-aulan which means to return to the origin. Some argue that ta'wil comes from the word yes, which means to arrange. There are also those who argue that Al-sharf means turning away and Al-siyasah which means tricking. The similarities between interpretation and ta'wil of the Qur'an are (1) The similarity of interpretation wa ta'wil of the Qur'an is actually seen in the target and objective of explaining the purpose and meaning of the verses of the al-Qur’an so that humans avoid mistakes in understanding the contents of the Qur'an as a way of life. Whereas (2) The difference between interpretation and ta'wil of the Qur'an is that ta'wil is an inner interpretation that is deeper than exegesis, but the condition for inner exegesis is that it corresponds to an outward interpretation which is more real and the meaning achieved by the exegesis cannot be expanded. with takwil especially in the interpretation of law.